Sensitivity of Grapevine Soil–Water Balance to Rainfall Spatial Variability at Local Scale Level - Bois, Benjamin; Pauthier, Basile; Brillante, Luca; Mathieu, Olivier; Leveque, Jean; Van Leeuwen, Cornelis; Castel, Thierry; Richard, Yves (Frontiers in Environmental Science, 2020)
In rainfed agriculture systems, rainfall water management (harvesting, storage and efficient use) is a key issue. At local scale (i.e. from 100m to 50 km), the impact of rainfall space and time variability on crop water availability is seldom addressed. In order to accurately depict the space and time variations of rainfall at local scale, a dense rain-gauges network composed of 45 rain-gauges has been deployed over 28 km² area, in Burgundy vineyards (North-East France). Rainfall data collected by each rain-gauge from 2014 to 2016 was used as input variables in the grapevine water balance model proposed by Lebon et al. All other climate variables, vineyard and soil parameters were kept strictly identical for each simulation in order to capture the consequences of the sole spatial variability of rainfall on vineyard water status. As rainfall dynamics impact on the vineyard depends on the soil water content, water balance was modelled considering soils with low (50 mm) and medium (150 mm) soil water holding capacities, representative of the soils of the area. The impact of modelled soil water availability for grapevine was assessed using the water deficit stress index (WDSI), i.e. the relative stomatal conductance. Local rainfall variability throughout the vine vegetative period lead to large variations in WDSI: it varied up to 0.3 within the study area solely because of rainfall spatial variability. Using a set of 34 weather stations at mesoscale level over Burgundy (186 km from North to South), we showed that local rainfall might contribute to change in grapevine water status as large as 50% of the simulated regional water balance spatial variability. Our results indicates that local rainfall and its impacts on agricultural production are probably not sufficiently considered in farming systems, potentially leading to in-accurate water management (cover-crop, irrigation) due to sparse rainfall network.